The Impact of Internal Governance Mechanisms on Tax Risk in Developing Countries: An Empirical Analysis - Mkadmi, Jamel Eddine; Say, Arem; Saida, Sana (International Journal of Economics and Financial Issues, 2022)
The purpose of this study investigates the impact of governance mechanisms, linked to the board of directors, on the tax risk of Tunisian listed companies. In order to empirically verify this relationship in the Tunisian context, we conducted a logistic regression with 8 banks listed on the Tunisian Stock Exchange during the period of 2008-2018. The overall results show that all the independent variables have a positive and non-significant impact on the probability of the presence of tax risk (with the exception of the dual management variable). Indeed, the variables size of the board of directors, the independence of its members and gender diversity have a positive and statistically insignificant impact on the probability of the presence of tax risk in Tunisian listed companies. On the other hand, the direction duality variable registers a positive and statistically significant correlation with the variable to be explained.